2018
DOI: 10.1177/2280800017750357
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical analysis and finite element simulation of fixator–bone system stiffness on healing progression

Abstract: Introduction: The unilateral external fixator has become a quick and easy application for fracture stabilization of the extremities; the main value for evaluation of mechanical stability of the external fixator is stiffness. The stiffness property of the external fixator affects the local biomechanical environment of fractured bone. Methods: In this study, a theoretical model with changing Young's modulus of the callus is established by using the Castigliano's theory, investigating compression stiffness, torsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…During exploration, external fixation device is loaded with complex stress, which can be considered as a combination of pressure, bending and torsion. In most of the studies of external fixation devices using FEM numerical methods or experimental methods, separated studies are done for: axial pressure testing, sagittal or anterior-posterior (AP) bending, and torsion [20][21][22][23]. The basic external load of external fixation device is axial pressure [24].…”
Section: Structural Analysis Of External Fixation Devicementioning
confidence: 99%
See 2 more Smart Citations
“…During exploration, external fixation device is loaded with complex stress, which can be considered as a combination of pressure, bending and torsion. In most of the studies of external fixation devices using FEM numerical methods or experimental methods, separated studies are done for: axial pressure testing, sagittal or anterior-posterior (AP) bending, and torsion [20][21][22][23]. The basic external load of external fixation device is axial pressure [24].…”
Section: Structural Analysis Of External Fixation Devicementioning
confidence: 99%
“…The main goal of usage of external fixation device is fast healing. From a literature review [20,27,28], it can be concluded that optimal biomechanical environment, for optimal healing of a bone, among other things, is based on the following two points of view: limited periodical axial displacements of bone segment at the fracture gap stimulate its healing after inflammation. This process is called dynamization.…”
Section: Structural Analysis Of External Fixation Devicementioning
confidence: 99%
See 1 more Smart Citation
“…These different external fixators, designed with different stiffness and stability characteristics, can be classified according to their frame configurations as unilateral, bilateral, quadrilateral, triangular, semi-circular, and circular [ 13 , 14 , 15 ]. The stiffness of the external fixators is critical to heal the fracture quickly and properly [ 9 , 16 ], but the optimal stiffness has not been identified yet. A more rigid frame can lead to a non-union or a delayed union, while a more flexible frame can lead to mal-union, non-union or pin–bone interface issues [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical performance of external fixation devices has been investigated by finite element analysis (FEA), considering either individual components of the frame or the entire assembled frame [ 16 , 18 , 19 , 20 ]. Sternick et al [ 21 ] used FEA to study the relationship between the stiffness of the external fixator and the number of pins and concluded that the stiffness of the fixator with four pins is 19% and 42% higher than the stiffness of external fixators with three and two pins.…”
Section: Introductionmentioning
confidence: 99%